2011
DOI: 10.1590/s0103-90162011000500003
|View full text |Cite
|
Sign up to set email alerts
|

Carbonate-silicate ratio for soil correction and influence on nutrition, biomass production and quality of palisade grass

Abstract: Silicates can be used as soil correctives, with the advantage of being a source of silicon, a beneficial element to the grasses. However, high concentrations of silicon in the plant would affect the digestibility of the forage. To evaluate the influence of the substitution of the calcium carbonate by calcium silicate on the nutrition, biomass production and the feed quality of the palisade grass [Urochloa brizantha (C. Hochstetter ex A. Rich.) R. Webster], three greenhouse experiments were conducted in complet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 22 publications
0
5
0
1
Order By: Relevance
“…The cultural practices were carried out according to CTCo protocol. Composite sample of soil was collected at 20 cm depth, to characterize the chemical and physical properties (Table 1), according to the methodology described by Souza et al, 2011. The rainfall during the experiment was 1,042 mm.…”
Section: Plant Growth and Nutrient Analysismentioning
confidence: 99%
“…The cultural practices were carried out according to CTCo protocol. Composite sample of soil was collected at 20 cm depth, to characterize the chemical and physical properties (Table 1), according to the methodology described by Souza et al, 2011. The rainfall during the experiment was 1,042 mm.…”
Section: Plant Growth and Nutrient Analysismentioning
confidence: 99%
“…Surface soil (0-20 cm depth) was collected from a non-cultivated field with natural Brazilian Cerrado vegetation. Later, after sieving through 4-mm mesh sieve, soil subsamples were characterized chemically, physically and mineralogically (Table 1), using the same methodology described in Souza et al (2011).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, for the proper development of the plants it is necessary to correct the soil. Lime application has been the main method for acidity correction because of its low cost, facility of application and increase of plant availability of Ca and Mg (Souza et al, 2011). However, in spite of being the most used corrective, the limestone has low mobility in the soil profile, slowing down the correction beyond the incorporation layer.…”
Section: Introductionmentioning
confidence: 99%
“…As a result of these benefits, silicates have been tested for use in acidity correction (Ramos et al, 2006) with the advantage of providing silicon to plants (Barbosa et al, 2008). Souza et al (2011) evaluated the effect of the substitution of calcium carbonate by calcium silicate on the palisade grass cultivated in soils with different textures and mineralogical composition. The authors found that the biomass production and feed quality of the palisade grass were generally higher with the 50% calcium silicate treatment.…”
Section: Introductionmentioning
confidence: 99%